Causal Associations Between Modifiable Risk Factors and the Alzheimer's Phenome. Issue 1 (15th October 2020) - Andrews, Shea J.; Fulton‐Howard, Brian; O'Reilly, Paul; Marcora, Edoardo; Goate, Alison M.; ,
Abstract : Objective: The purpose of this study was to infer causal relationships between 22 previously reported risk factors for Alzheimer's disease (AD) and the "AD phenome": AD, AD age of onset (AAOS), hippocampal volume, cortical surface area and thickness, cerebrospinal fluid (CSF) levels of amyloid‐β (Aβ42 ), tau, and ptau181, and the neuropathological burden of neuritic plaques, neurofibrillary tangles (NFTs), and vascular brain injury (VBI). Methods: Polygenic risk scores (PRS) for the 22 risk factors were computed in 26, 431 AD cases/controls and the association with AD was evaluated using logistic regression. Two‐sample Mendelian randomization (MR) was used to infer the causal effect of risk factors on the AD phenome. Results: PRS for increased education and diastolic blood pressure were associated with reduced risk for AD. MR indicated that only education was causally associated with reduced risk of AD, delayed AAOS, and increased cortical surface area and thickness. Total‐ and LDL‐cholesterol levels were causally associated with increased neuritic plaque burden, although the effects were driven by single nucleotide polymorphisms (SNPs) within the APOE locus. Diastolic blood pressure and pulse pressure are causally associated with increased risk of VBI. Furthermore, total cholesterol was associated with decreased hippocampal volume; smoking initiation with decreased cortical thickness; type 2 diabetes with an earlier AAOS; and sleep duration with increased cortical thickness. Interpretation: Our comprehensive examination of the genetic evidence for the causal relationships between previously reported risk factors in AD using PRS and MR supports a causal role for education, blood pressure, cholesterol levels, smoking, and diabetes with the AD phenome. ANN NEUROL 2021;89:54–65